Role of soluble triggering receptors expressed On myeloid cells (strem-1) in the pathogenesis Of periodontal disease - DR. CHANDNI S. NAIR; DR. DEVAPRIYA APPUKUTTAN; DR. D.J VICTOR; DR. RADHIKA B.N (International Journal of Pharma and Bio Sciences, 2017)
Periodontitis is a chronic inflammatory disease characterized by an exaggerated host response to microbes in plaque biofilm. A homeostasis is maintained between the oral bacteria and host response in health and any imbalance leads to dysregulated host immune-inflammatory response resulting in periodontal disease. Triggering Receptors Expressed on Myeloid cells-1 (TREM-1) is a signaling receptor present on myeloid cells which along with its adaptor protein DAP-12 acts synergistically with various pattern recognition receptors leading to amplification of inflammatory responses including upregulation of pro inflammatory mediators like TNF-α, Interleukin-8 and downregulation of anti-inflammatory mediators like Interleukin-10, Transforming growth factor β. Soluble (s)TREM-1, a subset of TREM-1 is also released from the cell surface during the course of infection both of which are useful inflammatory biomarkers in the early diagnosis of various chronic inflammatory conditions including periodontitis. This review gives an insight on the TREM biology including its genomic and structural organization, signaling pathway, function of TREM-1, soluble TREM-1 (sTREM-1) in modulating the inflammatory response during periodontal diseases and its potential use as an inflammatory biomarker.